Clinical Presentation and Anatomical Location of Orbital Plasmacytomas. Issue 3 (May 2018) - Thuro, Bradley A.; Sagiv, Oded; Shinder, Roman; Debnam, J. Matthew; Ozgur, Omar; Ng, John D.; Rootman, Daniel; Thomas, Sheeba K.; Esmaeli, Bita
Abstract : Purpose: To evaluate the clinical and anatomical location of orbital plasmacytomas and assess local control following therapy. Methods: The American Society of Ophthalmic Plastic and Reconstructive Surgery Oncology Database was queried to identify patients diagnosed with orbital plasmacytoma. These patients' records were reviewed for demographic characteristics, clinical and radiologic findings, treatments, and outcomes. Results: Thirty patients from 4 institutions (24 from MD Anderson Cancer Center, 3 from SUNY Downstate Medical Center, 2 from University of California, Los Angeles, and 1 from Oregon Health and Science University) were identified. Eighteen patients (60%) were diagnosed with multiple myeloma (MM) before and 11 (37%) were diagnosed with MM immediately after orbital plasmacytoma. Based on imaging, 4 distinct anatomical patterns were identified: 1) bony plasmacytoma affecting the superotemporal orbit, epidural space, and temporal fossa (15 patients; 50%); 2) discrete orbital plasmacytoma (7 patients; 23%); 3) infiltrative plasmacytoma either originating from a sinus (4 patients; 13%); or 4) originating from the orbital floor and infiltrating facial soft tissue (4 patients; 13%). Of the 29 patients with available treatment data, 2 had radiation only, 3 had chemotherapy only, 6 had chemoradiation, and 18 had stem cell transplant following chemoradiation (n = 17) or only chemotherapy (n = 1). Following treatment, 10 patients achieved complete and 11 achieved partial responses. Conclusion: Orbital plasmacytomas were found exclusively in patients with MM diagnosed before or immediately after orbital plasmacytoma. Plasmacytomas can have 4 distinct anatomical patterns of origin. Following treatment, all patients had good to excellent local control of their orbital lesions. Abstract : Orbital plasmacytomas have distinct clinical and radiologic features and a strong association with multiple myeloma; effective treatments for orbital plasmacytoma may include systemic chemotherapy, radiation therapy, or chemotherapy and radiation therapy in combination.